Pembuatan Sistem Informasi Akuntansi untuk UD. X - Tjokro, Albertus Leonardo; Yulia, Yulia; Setiabudi, Andy (Jurnal Infra, 2015)
UD. X, a car batteries trading business in Surabaya, is using manual accounting system. This old applied system canât provide any accurate financial report for owner. Furthermore, it has caused many human errors, inaccurate calculation, and irrelevant data service. As a solution, the company needs a computer based accounting system. The first step in creating a good accounting information system is to analyze and observe company working system. This new accounting information system needs to build an integrated modules of sales, purchases, and accounting. The new information system was build using Microsoft Visual Studio 2010 and SQL Server as database. The result obtained from the system are master recording, purchase and sale transaction recording, Â stock report, purchase report, sales report, general ledger, and financial statement such as income statement and balance sheet.